2015
DOI: 10.1155/2015/956046
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Implantation of Diffractive Multifocal Intraocular Lens in Eyes with Long Axial Lengths

Abstract: Purpose. This study retrospectively analyzed the postoperative visual functions of myopic eyes implanted with multifocal intraocular lens (IOL) to evaluate the efficacy of multifocal IOL in highly myopic eyes. Methods. We studied 61 patients (96 eyes) who were implanted with multifocal IOL ZMA00 or ZMB00 (Abbott Medical Optics). The patients were stratified into two groups by axial length: 26 mm or above (AL ≥ 26 group) and below 26 mm (AL < 26 group). Postoperative corrected and uncorrected distance (5 m) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
2
15
1
1
Order By: Relevance
“…However, as we have introduced, the use of multifocal IOLs for presbyopia correction in eyes with long axial lengths has been increasing due to the good outcomes reported previously by several authors using different IOL models. 12,13,15,16 Our results revealed good visual acuity outcomes for both groups of patients, long eye and nasal-inferior staphyloma. Safety and efficacy indexes were larger than 1.0 in all cases.…”
Section: Spherical Equivalent (D)supporting
confidence: 53%
See 2 more Smart Citations
“…However, as we have introduced, the use of multifocal IOLs for presbyopia correction in eyes with long axial lengths has been increasing due to the good outcomes reported previously by several authors using different IOL models. 12,13,15,16 Our results revealed good visual acuity outcomes for both groups of patients, long eye and nasal-inferior staphyloma. Safety and efficacy indexes were larger than 1.0 in all cases.…”
Section: Spherical Equivalent (D)supporting
confidence: 53%
“…Slight differences between studies may come from the use of a different multifocal IOL, different follow-up, and also for being higher myopic eyes in the case of Martiano and Cochener. 14 Ogawa et al 15 analyzed the 12-month postoperative outcomes found in 32 eyes implanted with the ZMA00 or the ZMB00 IOL. The mean axial length in this group was 27.38 mm, ranging from 26.06 to 29.24 mm.…”
Section: Spherical Equivalent (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alfonso et al [ 32 ] reported better results for distance and near VAs and CS in a group of low rather than highly myopic eyes after the implantation of the nontoric ReSTOR SN60D3 multifocal IOL (Alcon Laboratories Inc.). Ogawa et al [ 21 ] compared the distance and near VAs and CS of Tecnis multifocal IOL (Abbott Medical Optics, Inc., Santa Ana, CA) between eyes with an AL <26 mm and ≥26 mm and found no significant differences between groups. Neither study reported monocular intermediate VA or quantified visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…у пациентов с миопией высокой степени в исследовании T. Ogawa с соавт. [4] сообщается, что 81% пациентов (из 61 пациента, 96 глаз) обходились без использования очков в послеоперационном периоде.…”
Section: очковая независимость у пациентов после имплантации мультифоunclassified